Applications of 3D-Printed PEEK via Fused Filament Fabrication: A Systematic Review - Rupak Dua (MDPI AG, 2021)
Polyether ether ketone (PEEK) is an organic polymer that has excellent mechanical, chemical properties and can be additively manufactured (3D-printed) with ease. The use of 3D-printed PEEK has been growing in many fields. This article systematically reviews the current status of 3D-printed PEEK that has been used in various areas, including medical, chemical, aerospace, and electronics. A search of the use of 3D-printed PEEK articles published until September 2021 in various fields was performed using various databases. After reviewing the articles, and those which matched the inclusion criteria set for this systematic review, we found that the printing of PEEK is mainly performed by fused filament fabrication (FFF) or fused deposition modeling (FDM) printers. Based on the results of this systematic review, it was concluded that PEEK is a versatile material, and 3D-printed PEEK is finding applications in numerous industries. However, most of the applications are still in the research phase. Still, given how the research on PEEK is progressing and its additive manufacturing, it will soon be commercialized for many applications in numerous industries.